Meningkatkan Hasil Belajar PAI Melalui Model Problem Based Learning di UPTD SDN 12 Guguak VIII Koto - Kiki Yulia Muhtari; Salmiwati Salmiwati; Rina Mala Putri (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the existence of problems in learning Islamic Religious Education (PAI) in class IV UPTD SD Negeri 12 Guguak VIII Koto, namely in learning PAI teachers still teach conventionally have not utilized technology in learning so that learning becomes monotonous and outdated, teachers also have not applied a varied learning model, enthusiasm and motivation to learn PAI students are still lacking and the initiative to ask is still low. These problems resulted in low PAI learning outcomes of students. So that action is taken to overcome these problems by applying the Problem Based Learning model. The purpose of this study was to determine the improvement of PAI learning outcomes through the Problem Based Learning Model on the material of welcoming the age of puberty in class IV UPTD SD Negeri 12 Guguak VIII Koto District Guguak Kab Lima Puluh Kota. This type of research is a Classroom Action Research (PTK), which was conducted in two cycles. The subjects in this study were students of class IV SDN 12 Guguak VIII Koto in the 2024/2025 school year, totaling 13 people. The research success indicator determined is if the percentage of PAI learning outcomes is more than 75% of students get more than or equal to the Criteria for Achieving Learning Objectives (KKTP), namely 75. The results showed that teacher activities carried out in cycle I amounted to 75%, student activities were 78%, and the percentage of students' PAI learning outcomes was 62%. Although there was an increase in learning outcomes, it had not yet reached the predetermined success indicators so the research continued to cycle II. In cycle II, the teacher's activity was 100%, the students' activity was 96%, and the percentage of students' PAI learning outcomes was 92%. In cycle II, the success indicators were achieved so that the research did not need to be continued to the next cycle. The conclusion that can be drawn in this study is the increase in PAI learning outcomes through the Problem Based Learning model in class IV UPTD SD Negeri 12 Guguak VIII Koto Guguak District, Lima Puluh Kota Regency.